FOREIGN LANGUAGES DISTANCE LEARNING COURSE ORGANIZING AT A HIGHER EDUCATION INSTITUTION - Hohol, I. (Problems of Engineer-Pedagogical Education, 2021)
The article attempts to characterize the foreign languages distance learning as one of the innovative training formats, effectively complementing the existing intramural and extramural education at higher education institutions. The author emphasizes that the quality and effectiveness of foreign languages distance-learning course in higher education mainly depends on how effectively it is organized; from the teachers’ pedagogical skills, taking part in the training process; from the quality of methodological content, presented on the course. This work highlights the key principles of foreign languages distance learning at higher education institutions; the means of enhancing the quality and effectiveness of education this have been determined, the main conceptual provisions of foreign languages distance learning at a university have been determined. The article proposes a model for foreign languages distance learning course organizing for future specialists, presents a system for knowledge monitoring and controlling of all types of speech activity. It is also noted that the students’ independent work within the foreign languages distance course should not be passive, but on the contrary, the students should be involved in active cognitive activity; it is not limited to the foreign languages knowledge gaining, but necessarily involves their practical application; the students’ independent work is used to solve certain communication problems in the future professional activities. The conclusions of the article provide recommendations for the effective organization of foreign languages distance learning course at higher education institutions (careful selection of educational foreign language material based on the goals and objectives of the course, competent planning of the academic groups activity, regular individual and group reporting, constant consultations with a foreign language teacher) and etc. At the same time, it should be pointed out that in the process of the course organizing, in addition to the didactic characteristics and functions of multimedia and telecommunications as the technological basis of education, it is also necessary to take into account the conceptual tendencies of the didactic organization of distance learning as a component of the general modern educational system.